Efektivitas Keterampilan Vokasional Membuat Minuman Bandrek melalui Teknik Modeling bagi Anak Tunarungu Kelas X di SLB Negeri 1 Linggo Sari Baganti - Dini Hendriani; Fatmawati (Dinasti Research, 2021)
The purpose of this study was to prove that modeling techniques were effective in improving vocational skills in making bandrek drinks in class X deaf children at SLB Negeri 1 Lingo Sari Baganti. This type of research used is an experimental method in the form of pre-experimental with the type of one-group pretest-posttest design. then given treatment using modeling techniques and continued by giving a posttest processed and compared using the Wilcoxon Rank Test test. From the results of statistical test studies that have been analyzed using the SPSS 23 research program, the data obtained on average during the pretest was 54.40 while for the posttest there was an increase to 83.80. The data were processed more scientifically using the Wilcoxon test and obtained a rank test score between the pretest and posttest of 2.023 with Asymp. Sig (2-tailed) 0.043. Predetermined probability α = 0.05. The alternative hypothesis is accepted because the probability <of the probability that has been determined is 0.039 <0.05.